The extreme searcher's Internet handbook : a guide for the serious searcher - Hock, Randolph, 1944- (Medford, N.J. : CyberAge Books, 2004)
Provides ideas, techniques, and resources to effectively search the internet and is intended for librarians, teachers, students, writers, and professionals.
Includes index.
Adult
Keywords: Computer network resources -- Handbooks, manuals, etc; Internet addresses -- Directories; Internet searching -- Handbooks, manuals, etc; Web search engines -- Handbooks, manuals, etc; Web sites -- Directories; Internet addresses -- Directories; Internet resources -- Handbooks, manuals, etc; Internet searching -- Handbooks, manuals, etc; Web search engines -- Handbooks, manuals, etc; Web sites -- Directories